Nerve detection with optical spectroscopy for regional anesthesia procedures - Hendriks, Benno H. W. (J Transl Med, 2015)
BACKGROUND: Regional anesthesia has several advantages over general anesthesia but requires accurate needle placement to be effective. To achieve accurate placement, a needle equipped with optical fibers that allows tissue discrimination at the needle tip based on optical spectroscopy is proposed. This study investigates the sensitivity and specificity with which this optical needle can discriminate nerves from the surrounding tissues making use of different classification methods. METHODS: Diffuse reflectance spectra were acquired from 1563 different locations from 19 human cadavers in the wavelength range of 400–1710 nm; measured tissue types included fascicular tissue of the nerve, muscle, sliding fat and subcutaneous fat. Physiological parameters of the tissues were derived from the measured spectra and part of the data was directly compared to histology. Various classification methods were then applied to the derived parameter dataset to determine the accuracy with which fascicular tissue of the nerve can be discriminated from the surrounding tissues. RESULTS: From the parameters determined from the measured spectra of the various tissues surrounding the nerve, fat content, blood content, beta-carotene content and scattering were most distinctive when comparing fascicular and non-fascicular tissue. Support Vector Machine classification with a combination of feature selections performed best in discriminating fascicular nerve tissue from the surrounding tissues with a sensitivity and specificity around 90 %. CONCLUSIONS: This study showed that spectral tissue sensing, based on diffuse reflectance spectroscopy at the needle tip, is a promising technique to discriminate fascicular tissue of the nerve from the surrounding tissues. The technique may therefore improve accurate needle placement near the nerve which is necessary for effective nerve blocks in regional anesthesia.